Andexanet Alfa for Specific Anticoagulation Reversal in Patients with Acute Bleeding during Treatment with Edoxaban - Benz, Alexander P.; Xu, Lizhen; Eikelboom, John W.; Middeldorp, Saskia; Milling, Truman J., Jr.; Crowther, Mark; Yue, Patrick; Conley, Pamela; Lu, Genmin; Connolly, Stuart J.; on behalf of the ANNEXA-4 Investigators (Thrombosis and Haemostasis, 2022)
Background Andexanet alfa (andexanet) is approved for specific anticoagulation reversal in patients with life-threatening or uncontrolled bleeding during treatment with rivaroxaban or apixaban. There is limited experience with andexanet in patients with acute bleeding on edoxaban.Methods Patients with acute major bleeding within 18 hours of edoxaban intake were prospectively enrolled. Patients received a bolus and 2-hour follow-on infusion of andexanet. The co-primary efficacy outcomes were change in antifactor Xa activity and the percentage of patients achieving excellent or good hemostasis, 12 hours after andexanet treatment. Efficacy was analyzed in patients with confirmed major bleeding and baseline antifactor Xa activity ≥40 ng/mL. Safety was analyzed in all patients.Results Thirty-six patients (mean age: 82 years, 61.1% male and 91.7% with atrial fibrillation) with acute major bleeding on edoxaban received andexanet. The primary site of bleeding was intracranial in 29 patients (80.6%). In the efficacy population (n = 28), median antifactor Xa activity decreased from 121.1 (interquartile range [IQR]: 70.3–202.4) ng/mL at baseline to 24.0 (IQR: 77.7–83.7) ng/mL at the end of andexanet bolus (median decrease: 68.9%, 95% confidence interval [CI]: 56.1–77.7%). Excellent or good hemostasis at 12 hours was achieved in 78.6% (95% CI: 59.0–91.7%) of patients. Within 30 days, four patients (11.1%) experienced a thrombotic event and four others (11.1%) died.Conclusion In patients with acute major bleeding on edoxaban, andexanet significantly decreased antifactor Xa activity. Hemostatic efficacy was similar to that observed in patients with bleeding on rivaroxaban or apixaban. Thrombotic events occurred at a rate expected in such patients.
Keywords: andexanet alfa; reversal; edoxaban; intracranial hemorrhage; bleeding